Prognostic significance of pituitary tumour-transforming gene-binding factor (PBF) expression in papillary thyroid carcinoma - Hsueh, Chuen; Lin, Jen-Der; Chang, Yu-Sun; Hsueh, Swei; Chao, Tzu-Chieh; Yu, Jau-Song; Jung, Shih-Ming; Tseng, Ngan-Ming; Sun, Jui-Hung; Kuo, Shau-Yun; Ueng, Shir-Hwa (Clinical endocrinology (Oxford), 2013)
Summary Background Pituitary tumour‐transforming gene (PTTG)‐binding factor (PBF), originally known as PTTG1 interacting protein (PTTG1IP), has been found to be significantly increased in well‐differentiated thyroid cancer and independently associated with early tumour recurrence. Objective To assess the prognostic significance of PBF expression in a large cohort of papillary thyroid carcinoma (PTC) patients with a long‐term follow‐up. Design and patients Retrospective analysis of PBF expression in PTC cases at different stages and correlate it with various clinicopathological parameters and patient survival. Subjects included 153 patients who received a thyroid operation for PTC at Chang Gung Memorial Hospital between 1991 and 2000. All patients had a complete follow‐up till the end of 2010. Measurements Immunohistochemical study for PBF expression on tissue sections from tumour specimens. Bond automated machine (Leica Microsystems, Germany) with a polyclonal rabbit anti‐PBF antibody (LifeSpan BioSciences, LS‐C118942, Seattle, WA, USA) was used. SPSS 13.0 for Windows (SPSS Inc, Chicago, IL, USA) was used for all statistical analyses. Results High PBF expression was significantly correlated with age (P = 0·0298), distant metastases at diagnosis (P = 0·0139), tumour multicentricity (P = 0·0035), TNM stage (P = 0·0103), locoregional recurrence (P = 0·0410) and disease‐specific mortality (P = 0·0064). The expression level of PBF was significantly correlated with disease‐specific survival (P = 0·0065). Cox regression analysis showed that age, tumour size and PBF expression were independent prognostic indicators (P = 0·0097, P = 0·0021 and P = 0·0179). Conclusion PBF expression may be a promising biomarker for prognostic and therapeutic purpose. More large‐scale studies are needed to clarify its potential usefulness.